COMPARISON OF AN EXPERIMENTAL ROOT CANAL IRRIGANT (SAPINDUS MUKOROSSI) AND ETHYLENEDIAMINETETRAACETIC ACID ON MICROHARDNESS OF HUMAN DENTIN - Farooq, Asad; Fazal Ur Rehman Qazi; Juveria Siddique; Syed Abul Faraz; Abdur Rasheed (Journal of Ayub Medical College Abbottabad, 2022)
Background: The treatment of infected root canals is one of the most essential areas in dentistry. The endodontic therapy comprises of a sequence of steps that includes the purging of disease and infectious tissues from the root canal system. The objective of the study is to compare the effect of an experimental herbal root canal irrigant (Sapindus mukorossi) and Ethylenediaminetetraacetic acid, on the micro hardness of human dentin. Methods: Ninety single rooted teeth were collected displayed intact external morphology the selected teeth were than divided randomly into 3 groups (n=30); 1 control and 2 experimental groups: Group A consisted of specimen treated with Ethanolic extract of Sapindus mukorossi. Group B consisted of specimen treated with 17% Ethylenediaminetetraacetic acid and Group C (control group) consisted of specimen of roots were sectioned immersed in distilled water. After the removal of crowns, the roots were sectioned embedded in the polymer resin leaving the root dentine exposed, the micro hardness was determined. Then, the samples from each group were treated with respective irrigant solution for 15 minutes and then observation regarding the micro hardness were noted again by using Vickers micro hardness tester. Analysis of data were obtained by application of Wilcoxon signed rank test. Results: The study revealed that there was no significant difference noted in dentin microhardness of group A sample after dipping in experimental irrigant solution (Sapindus mukorossi). However, the study found significant difference in context of decrease in dentin microhardness after dipping a sample in a group B irrigant solution (17% Ethylenediaminetetraacetic acid). Conclusion: In order to preserve the strength of dentin that will ultimately be beneficial for increase in survival of teeth in function, probably the herbal extract of Sapindus mukorossi would be better candidate for future endeavour and presented as an economic and effective alternative amongst root canal irrigants.